The unequal contribution of urban blue-green space to the cooling effect - Li, Xiaoming; Fan, Chenchen; Sun, Xiaohan; Li, Wenwen; Lu, Jieqiong; Bao, Guanglong; Yan, Fei (Frontiers in Environmental Science, 2025)
Clarifying the contribution of urban blue-green spaces to the cooling effect on surface temperature is crucial for rationalizing urban land use and ensuring sustainable urban development. This study examined how blue-green spaces have changed over time and how these changes affect land surface temperature (LST) in 41 prefecture-level cities in China’s Yangtze River Delta (YRD) region from 2000 to 2024. The researchers used remote sensing data and landscape indices, employing Moran’s I and Geographically and temporally weighted regression (GTWR) models, to analyze the relationship between blue-green spaces and LST in the YRD. During the study period, LST increased significantly in most cities, notably in Hefei and Nanjing. Blue-green space areas decreased and fragmented; for instance, Hefei’s green space area shrank from 9,665.44 km2 to 5,726.63 km2. The GTWR model revealed that blue-green space landscape indices (such as PD, ED, and CONTAG) influence LST spatial heterogeneity. Highly fragmented blue-green spaces in the southern region may reduce LST, while those in the northwestern region may increase it. In the southern YRD, the presence of abundant water bodies alongside highly fragmented blue-green spaces may reduce LST by enhancing evapotranspiration and creating cooling islands. By contrast, in the northwestern YRD, where water bodies are fewer, fragmentation of blue-green spaces is associated with an increase in LST, since the cooling capacity of green spaces alone is insufficient. Optimizing the layout of blue-green spaces and integrating their synergistic effects could significantly enhance cooling capacity and reduce inequalities in contributions to cooling effects.